Umbilical arterial flow analysis to determine an index of placental impedance - Wright, Andrew William (Division of Biomedical Engineering, 2018)
Umbilical flow velocity waveforms (FVW' s) can be measured non-invasively using Doppler ultrasound. Changes in the FVW's occur long before the warning signs from other conventional monitoring methods. Correct interpretation of the changes in the FVW has the potential of providing the clinician with an early warning of foetal distress. A number of indices have been described in the literature to characterise the FVW including the Pulsatility Index (PI), the Resistance Index (RI) and more recently, the High Resistance State Index (HRSI). Researchers have shown a dependence of the FVW, and thus the indices which describe it, on factors such as the placental resistance (Muijsers et al 1990a) blood pressure pulsatility (Mulders et al 1986), and the foetal heart rate (Downing et al 1991). In order to model the foetal circulation, the dimensions of the foetal vessels were required. These were taken from the literature when available, but had to be supplemented by measurements on post mortem specimens. This information, together with blood pressures and flow rates taken from the literature, was used to design electrical analogous models of the foetal arterial circulation (model 1 and model 2), which were implemented using PSpice, which is an electronic circuit simulator package. The Flow Velocity Waveforms (FVW's) simulated were stored and then analyzed using MATLAB, which is a mathematical package to calculate the waveform indices and both the blood pressure and percentage blood flow to the different anatomical regions of the foetus. Model 1 is a simple model of the umbilical placental unit only, which assumes a rectified sine wave with a D.C. offset as an input waveform while Model 2 is a distributed element model of the complete foetal arterial system, including a realistic representation of the foetal heart. AIM: Simulations of the FVW were used to examine the effects of placental obliteration (raised placental resistance), placental size, foetal heart rate (FHR), blood pressure pulsatility (BPPI), mean blood pressure (BP), and site of measurement of the FVW along the umbilical artery and thus on the waveform indices which are used to describe it (RI, PI and HRSI). RESULTS/ DISCUSSION: The investigations using models 1 and 2 showed that the indices were significantly dependent on the placental resistance, the size of the placenta and the type of placental obliteration. Model 1 was also used to investigate the effect of FHR variations on the indices under the original assumption that the input waveform to the umbilical/placental unit was a rectified sinusoid offset by a constant voltage (D.C.) (Thompson and Trudinger 1990). The result obtained, that is, the FHR does not affect the indices (in particular the PI) needed further investigation because the assumption for the input waveform is not true under all conditions. For this reason, the simulations were repeated using model 2, with the interesting result that there is a difference between short term FHR variations and long-term FHR variation. Short term FHR variations had a pronounced effect on the indices. The blood pressure pulsatility and the indices concerned varied by large amounts in this case, which indicated a link between the blood pressure pulsatility and all the indices. Long term FHR variations had an inconsistent but small effect on the blood pressure pulsatility and in turn had a small effect on the RI and PI. The mean blood pressure in these simulations decreased with increasing FHR which resulted in a pronounced increase in the HRSI which indicated the dependency of this index on the mean blood pressure rather than on the blood pressure pulsatility. It was found that the HRSI is a good index of placental resistance and may be particularly useful in evaluating high placental resistance in cases of absent flow during diastole, since, in these cases it is only slightly affected by the FHR. A value of greater than 34 percent is the recommended HRSI value to indicate severe foetal distress. The results also indicate that the FVW shape varies along the umbilical artery and is far more pulsatile at the aortic (proximal) end than the placental end. This is reflected in the indices which thus have worst case values at the placental end. It is thus recommended that, where possible, the indices are measured at the placental end of the umbilical artery.